Construction Of The Wienberg Equation For The Eigenvectors Of The Family Of Operator Matrices (Eurasian Journal of Physics,Chemistry and Mathematics, 2024)
In this paper we consider the family of operator matrices H (K) of order three which depends on the parameter K. This family of operator matrices are act in the three-particle cut subspace of the bosonic Fock space. We constract the Weinberg equation for the eigenvectors of H (K).